Analisis Kompetensi Sosial Guru Kelas Sebagai Motivator Untuk Membiasakan Karakter Kedisiplinan Siswa Kelas 5 Di SDN Taraman 1 - Mulatsih, Retno Anjar; , Drs.H.Mulyadi Sri Kamulyan,S.H, M.Pd (2017)
This study aims to: 1) Determine the social competence of teachers can memperangaruhi grade teacher as motivator, 2) To describe the social competence of classroom teachers as a motivator can familiarize Grade 5 student discipline code SDN Taraman 1. This research uses descriptive qualitative approach with case study design. Informants in this study is the Principal and Teacher Classroom 5. Data collection techniques used were interviews, observation, and documentation. Data analysis techniques include interactive analysis model which has three components: data presentation, data reduction and conclusion or verification. The validity of research data using a triangulation of sources and triangulation techniques / methods. The results showed that 1) Social competence of teachers can affect 5th grade teacher as a motivator by providing the motivation, make students who used to often come too late, naughty, cheating can be turned into student discipline, and now a lot of students who themselves have been put through things posisitif such as taking out the trash in its place thanks to imitate the teacher that every day is always tidy and dispose of waste in place. 2) The influence of social competence as a motivator classroom teachers to discipline students in grade 5 SDN Taraman 1 is to give motivation to discipline the form of words and actions against students during lessons and break lasts